FOOD AND FEEDING HABITS OF Clarotes laticeps (RÜPPEL, 1829) FROM LAKE AKATA, BENUE STATE, NIGERIA - IKONGBEH, O.A.; OGBE, F.G.; SOLOMON, S.G. (Nigerian Journal of Fisheries, 2012)
Food and feeding habits of Clarotes laticeps (Rüppel, 1829) were investigated in Lake Akata, Benue State, Nigeria. Samples were collected from May 2008 – April 2009. Eighty nine fish specimens were examined and their stomach contents analyzed. Food and feeding habits were investigated using point and frequency of occurrence methods. The seasonal variation, changes in the dietary composition with size and monthly feeding index were also noted in the stomach contents of C. laticeps. Close examination of the individual food items showed that insects, crustaceans, fish and molluscs were the most important food that occurred most frequently. The food items suggested that C. laticeps was a predator with preference for insects and crustaceans.